Coastal ridge constructive processes at a multi‐decadal scale in Barreta Island (southern Portugal) - Herrero, Xabier (2021)
Multiple ridges across prograding coasts may display variable geometries, commonly expressed through varying elevations. Changes in ridge elevation have been traditionally related to the occurrence of fluctuating progradation rates, which might, in turn, be driven by shifting environmental conditions. Here, we explore the geometry and growth mechanisms of multiple ridges, generated at Barreta Island (Ria Formosa, southern Portugal), as a consequence of the rapid progradation of the island over the last 70 years, following the artificial fixation of the downdrift Faro-Olhao inlet with jetties in 1955. The variability in the morphology of these features was analysed in combination with available wind and wave data, in order to better distinguish growth mechanisms and understand the main parameters determining the final geometry of the observed ridges. The results suggest that (1) most of the identified ridges fall in the beach ridge classification, as they have been mostly built by marine processes, and (2) the parameters derived from, or closely related to wave climate variability (e.g. progradation rates, storm occurrence) can jointly explain most of the observed morphological changes, while aeolian processes played a secondary role. Indeed, ridge geometry appears mainly controlled by progradation rates, with higher ridges associated with lower progradation rates. Progradation rate, in turn, is mostly related to longshore wave power, storminess, and the occurrence storm groups. Yet, the final configuration of ridges can also be affected by runup levels and onshore winds. Therefore, establishing the relation between ridge geometry and wave climate is not a straightforward task, because of the complex processes and interactions that control coastal morphodynamics.